Need Analysis for Teacher Performance Evaluation: Systematic Literature Review - Usman, Errina; Hakim Irwanto, Moch. Surya; Zainiyati, Husniyatus Salamah; Suryani, Suryani (Universitas Muhammadiyah Magelang, 2023)
One of recent educational problems is in the evaluation of teacher performance. It is revealed that the practices of teacher performance evaluation are manual, intuitive, and less objective. It causes the evaluation of teachers’ performance has not been maximum. This inability to carry out teacher performance evaluation must be analyzed in order to minimize evaluation practices that do not comply with procedures, so as to produce maximum assessments as material for sustainable evaluation. The aim of this research is to analyze the needs for teacher performance assessment practices in Indonesia. This research uses a qualitative approach of the systematic literature review (SLR) type. The tools used to compile literature are Publish and Perish and Google Scholar. The codification results find 25 articles about teacher performance evaluation. The codified articles are limited from 2018 -2022. The research results show that the most urgent need analysis is the requirement for teacher performance evaluation to determine the teacher's ability to do their responsibilities and to provide warnings and motivation to teachers. Good teachers are supported by the competence of good school principals as mentors, coaches, and developers in school progress.